Detection and Investigation of Counterfeit Medical Products in Slovenia* - Slak, Boštjan; Frangez, Danijela (Kriminologijos studijos, 2023)
This article provides insights into the detection, investigation and prosecution of counterfeit medical products in Slovenia and abroad. The article summarizes the reports of Interpol and the European Union’s activities in this area. It also uses the opinions and insights of experts in the field provided through interviews. While the scope of the problem surrounding counterfeit medical products has been increasing globally, the issue is not alarming in Slovenia. Counterfeit medical products (CFMP) were never found to enter the legal supply chain in Slovenia. In general, the incidence of counterfeit medical products in the scope of detection, investigation and prosecution is extremely low. The reasons for this may be in the ongoing debates about the definition of CFMPs and the continuing lack of public awareness about counterfeit medical products. If the public does not understand or even know about counterfeit medical products, they will fail to report potential encounters with them, thus making their detection even more difficult. The research study presented in this paper has (partly) confirmed that a sound and socially-oriented healthcare system in which the required medicines are widely available represents a deterrent against counterfeit medical products. Therefore, the legislative framework supporting such a system is most important.
Keywords: counterfeit medical products; detection; investigation; prosecution